Hepatoprotector Effect of Moringa Oleifera Lam. Seeds Extract Through Decrease Liver Inflammation of Rats with Metabolic Syndrome - Rezkita, Bastomy Eka; Pertiwi, Ina Agustin; Dhelima, Ismi Cahya; Budiani, Dyah Ratna; Irving, Steven (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Metabolic syndrome has been associated with chronic inflammation due to the increase of lymphocyte focus on hepatic lobular tissue. Moringa oleifera Lam. is an herbal plant that potentially reduce the inflammation process. This study aims to evaluate the effect of Moringa seed extract (MSE) on hepatic lobularinflammation in rats with hepatic tissue metabolic syndrome (MetS).Method: Twenty-four male Wistar rats (n = 24) were assigned into four groups: one control group (C) and three MetS groups, fed with a high-fat, high-fructose diet (HFHFD) daily for 53 days. After 53 days, respectively, MetS 2 and MetS 3 groups were given 150 and 200 mg/kg MSE. After 28 days of MSE administration, the rats were sacrificed, and then hepatic lobular inflammation measured with lobular inflammation score. The effect of MSE on hepatic lobular inflammation was analyzed with Kruskal-Wallis and Mann-Whitney test.Results: There was a significant difference in hepatic lobular inflammation between four groups (p = 0.000). Mann-Whitney showed a significant difference between C vs. MetS 1, MetS 1 vs. MetS 2, and MetS 1 vs. MetS 3 (p = 0.000), but not significant C vs. MetS 2 (p = 0.364), C vs. MetS 3 (p = 0.109), MetS 2 vs. MetS 3 (p = 0.533).Conclusion: MSE at the dose of 150 mg/kg and 200 mg/kg significantly reduces lobular inflammation in hepatic tissue of MetS rats.